The Role of Financial Risks and Financial Sustainability in the Iraqi Stock Markets during COVID-19 Pandemic - Almayyahi, Aymen Raheem Abdulaali (Journal of Asian Multicultural Research for Economy and Management Study, 2023)
This paper compares the company's ability to sustain a diversified resource base for long-term service to its customers without need for external funding sources through two stressful systems of financial markets, the financial crisis aftermath 2008 and the COVID-19 epidemic. Our findings indicate that financial sustainability has been affected by disasters. Banks can impose significant risks on the economy, one of the main concerns about the causes of the current financial crisis is that banks engaged in excessive risk-taking, it has faced during the 2008 crisis liquidity and credit risks, while Through the 2020 crisis which is the COVID-19 pandemic crisis, the most significant financial risks that banks experienced were credit risks due to banks ’dependence on traditional, weak, safe assets, including the dollar, the Swiss franc, and other treasury bonds during the COVID-19 pandemic. This led to a lack of cash reserves held by banks, which led to weak investor tolerance towards financial risks, especially as the nature of crises is changing, as the results have proven that departures from riskiest directorships are more beneficial during the COVID-19 crisis because managers deal with the crisis in the same way as a crisis 2008 On the other hand, departures from riskiest directorships lead to higher administrative costs due to a lack of expertise.